Primary mediastinal large B‐cell lymphoma: Outcome of a series of pediatric patients treated with high‐dose methotrexate and cytarabine plus anti‐CD20. Issue 2 (19th October 2017) - Pillon, Marta; Carraro, E.; Mussolin, L.; Conter, V.; Tondo, A.; Aricò, M.; Mura, R.; Sala, A.; Vinti, L.; Buffardi, S.; Pierani, P.; d'Amore, E. S. G.; et al.
Abstract: Between 2007 and 2013, 13 children diagnosed with primary mediastinal large B‐cell lymphoma (PMLBL) were treated according to a modified version of AIEOP (Associazione Italiana Ematologia Oncologia Pediatrica) LNH‐97 protocol based on high‐dose methotrexate, anthracyclines, and addition of anti‐CD20. Ten patients achieved a continuous complete remission with front‐line therapy. The overall 5‐year survival was 91.7%, and event‐free survival was 83.9%, with only one patient dying of progressive disease. Despite the few cases, these results demonstrate that this therapy, which includes anti‐CD20, given in a multicenter setting, is feasible with acceptable toxicity in children with PMLBL.